"Good soldiers and even heroes"; or From the history of the Roma in Croatia and Slavonia during the First World War. Issue 1 (June 2020) - VOJAK, DANIJEL
Abstract : There are few known historical sources to show what position minority and sociopolitically marginalized groups such as the Roma population held in Croatian territory during the First World War. Due to the above, but also due to a lack of scientific and public interest, this subject has been neglected in the Croatian historiography. This work is based on the analysis of archival sources and other relevant secondary literature with the goal of researching the relationship between the state (especially army) and local authorities' position towards the Roma in Croatian territory in the period from 1914 to 1918. Research on the position of the Roma in Croatian and Slavonian territory during the First World War has shown that their social status generally worsened during this period. Roma fit for military service were mobilized into the Austro-Hungarian army, and a number of these sought to desert. At the same time, Croatian state and local authorities placed the Roma in a category of particularly suspicious persons, thus seeking to carefully monitor their wanderings. A certain fear of the nomadic Roma as "permanent foreigners" and those who continuously resist the pressure of sedentarization and social integration motivated these authorities to enact general provisions to regulate the rights and responsibilities of the Roma during the war. In this context and under the influence of similar regulation enacted in Hungary, the Croatian government council enacted a provision on the sedentarization of the nomadic Roma in August 1916 which, among other things, included measures that forcibly tied them to a place of residence and controlled their wanderings and employment.